Childhood health and the wantedness of male and female children - Palloni, Giordano (Elsevier, 2017)
Maternal desire for children of a particular sex has important implications for the well-being of household members. A simple theoretical model predicts that when a child is born of their mother's preferred sex, parents will allocate more resources towards that child, resulting in healthier children. I test this prediction empirically using a longitudinal data set from Indonesia. Each mother's preferred sex, defined by whether she prefers for future children to be male or female, is matched to the observed sex of her subsequent child. Because this measure of maternal sex preference is established before conception, identification requires only that the sex at birth of the subsequent child is random. I find that children born of their mother's preferred sex are heavier, have a higher body mass index, and experience fewer illnesses in early childhood. I show that reductions in subsequent fertility can explain roughly half of the total effect.